Tertullian the Carthaginian: North African Narrative Identity and the Use of History in the Apologeticum and Ad Martyras - Perkins, Alexander D. (Journal of Early Christian Studies, 2020)
Recent scholarship has begun to consider more seriously the effects of Tertullian of Carthage’s status as a colonized subject on his oeuvre. This article builds upon this groundwork, addressing Tertullian’s relationship to his North African identity by analyzing his use of Roman and North African history in his apologetic works. In particular, it examines Tertullian’s deployment of the Roman historiographic trope of exempla, narrative vignettes designed to emphasize the ideological goals of the historian, in the Apologeticum and his letter Ad Martyras with his colonial status in mind. Tertullian draws on certain exempla from the historical relationship between Carthage and Rome that prior Roman historians often used to bolster Rome’s claim to the divine right to rule. He reframes these stories in a manner that undermines these claims and places North Africa at the center of the historical narrative. In this way, Tertullian presents a view of history that privileges a North African narrative identity in which local Christians, especially martyrs, could imagine themselves as the latest participants.
paid